Work Culture in Improving Vocational Student Performance in Hybrid Learning Adaptation Post Covid-19 Pandemic - Nurillah Jamil Achmawati Novel; Tribowo Rachmat Fauzan; Nenden Kostini (Jurnal Kajian Ilmu Pendidikan (JKIP), 2023)
The COVID-19 pandemic has encouraged adaptation in various sectors, one of which is education through hybrid learning. This study aims to determine the effect and level of work culture application on vocational students' performance in adapting hybrid learning after the COVID-19 pandemic. Mixed research methods were used to collect relevant data and process data qualitatively and quantitatively. The results of this study indicate a significance level of less than 0.05, which means that the regression model can predict work culture variables with a coefficient of determination of 66.8%. So it can be concluded that there is a significant influence of work culture variables on the performance of vocational students in adapting hybrid learning after the COVID-19 pandemic by implementing work culture and producing excellent performance.